Hydrogen generation with CO2 utilization: a solvay cluster study - Kale, Ganesh R.; Kulkarni, Bhaskar D. (International Journal of Hydrogen Energy, 2013)
The fuel cell economy is yet to start research programs in hydrogen generation with CO2 utilization for hydrocarbon reforming processes used in fuel processor applications. A simple thermodynamic study using solvay clusters was done to investigate the feasibility of using the carbon species produced in the steam methane reforming process to produce value added chemicals. The results of this study are highly encouraging to start process development of closed systems of hydrogen generation with CO2 conversion to acetic acid/acrylic acid making easier the commercialization of fuel cells and hydrogen energy. Such studies can be specifically carried out for different fuel processor systems. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CO2 utilization; Fuel processing; Gibbs energy; Solvay clusters; Steam reforming